Insights Into the Involvement of Circular RNAs in Autoimmune Diseases - Zhai, Xingyu; Zhang, Yunfei; Xin, Shuyu; Cao, Pengfei; Lu, Jianhong (Frontiers in Immunology, 2021)
Circular RNAs (circRNAs) are single-stranded, endogenous, non-coding RNA (ncRNA) molecules formed by the backsplicing of messenger RNA (mRNA) precursors and have covalently closed circular structures without 5′-end caps and 3′-end polyadenylation [poly(A)] tails. CircRNAs are characterized by abundant species, stable structures, conserved sequences, cell- or tissue-specific expression, and widespread and stable presence in many organisms. Therefore, circRNAs can be used as biomarkers for the prediction, diagnosis, and treatment of a variety of diseases. Autoimmune diseases (AIDs) are caused by defects in immune tolerance or abnormal immune regulation, which leads to damage to host organs. Due to the complexity of the pathophysiological processes of AIDs, clinical therapeutics have been suboptimal. The emergence of circRNAs sheds new light on the treatment of AIDs. In particular, circRNAs mainly participate in the occurrence and development of AIDs by sponging targets. This review systematically explains the formation, function, mechanism, and characteristics of circRNAs in the context of AIDs. With a deeper understanding of the pathophysiological functions of circRNAs in the pathogenesis of AIDs, circRNAs may become reasonable, accurate, and effective biomarkers for the diagnosis and treatment of AIDs in the future.